Assessment of wine tourism potential in the countries of the former Yugoslavia. - Jovanovic, Radmila; Almeida-García, Fernando; Cortés-Macías, Rafael; Parzych, Krzysztof (Elsevier, 2025)
We conducted a study on the tourism potential of the wine-growing areas of the countries of the former Yugoslavia, a region that has undergone extensive economic and political changes. We propose a new analysis model based on the open data for the evaluation of the tourism potential in wine-growing areas and wineries. For the research purposes, open geodata available through Open Street Maps, Google Maps, CORINE Land Cover, Digital Elevation Model and official databases of the countries analysed were taken. The tourism evaluation of the potential was carried out using a multicriterial method and the Geographic Information System. The variables linked to the wine tourism activity are grouped into six main tourism factors (cultural attractions, accommodation offer, etc.). On the other hand, the potential for wine tourism in the vineyard areas and winery are calculated, and the results are translated into maps that identify the tourism variables and are captured in three potential maps: Tourism factors, Vineyards and Wineries. i) Tourism factor results highlight the areas with a high tourism potential that have a close connection with some tourism resources (sea, natural and heritage areas). The best scores were obtained in the wine-growing areas of Croatia and Slovenia, especially those located near the sea. ii) Vineyard areas with a high level of wine tourism are located in the similar areas, Dalmatia, Istria and border areas between Slovenia and Croatia. iii) Wineries with high tourism potential are located in Dalmatia and the Danube valley around Belgrade, and areas of Montenegro.
Los resultados expuestos en la publicación forman parte de la tesis de Radmila Jovanović. Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/35822
Keywords: Enoturismo - Yugoslavia; Open data; Tourism potential; Wine tourism; Yugoslavia; Rural development